IMPACT OF COVID-19 PANDEMIC ON STOCK PRICE VOLATILITY OF SUB-SECTOR INDICES IN THE NIGERIAN STOCK EXCHANGE - Oyewale Temilola Christiana; Muftau Adeniyi Ijaiya; Kasali Kayode Rafiu (Malete Journal of Accounting and Finance, 2022)
Stock market volatility influences investor’s participation in the stock market of any nation. The global pandemic created a lot of uncertainty about future of the economy, especially among developing stock market, like the Nigerian stock market. The emergence of COVID-19 pandemic impacted different sectors of Nigeria's economy in diverse ways and this affected investor’s confidence in the Nigeria stock market. This study investigated the impact of COVID-19 pandemic on the sub-sector indices in the Nigeria stock exchange market. The study employed ex-post facto research design to determine the impact of COVID-19 infection rates and COVID-19 death rates on stock price volatility of sub-sector indices in the Nigeria stock exchange market, within the period of 2nd March 2020 to 28th February, 2022. The study employed GARCH and DCC-GARCH and found that COVID-19 pandemic (infection and death rates) had significant effect on the volatility of sub-sector indices in the Nigeria stock market, and that there was significant volatility transmission among the sub-sector indices of the Nigerian stock market during the COVID-19 pandemic period. The study recommends that policy makers should provide support to companies that were badly hit during the pandemic, and also encouraged portfolio managers to understand the nature of risk attached to stocks selected to be in portfolio of their investors and be aware of best way to mitigate adverse risk effect.